2006
DOI: 10.3168/jds.s0022-0302(06)72395-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Dairy Cow Diet Forage Proportion on Duodenal Nutrient Supply and Urinary Purine Derivative Excretion

Abstract: Four mature Holstein-Friesian dairy cows were used in a 4 x 4 Latin square change-over design experiment made up of four 4-wk periods to investigate the relationship between microbial protein flow to the duodenum and excretion of purine derivatives (PD) in the urine. Four dietary treatments based on ad libitum access to ryegrass silage were offered, with a standard dairy concentrate included at different forage:concentrate (F:C) ratios, calculated on a dry matter basis: 80:20, 65:35, 50:50, and 35:65. Feed int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
92
6
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(114 citation statements)
references
References 40 publications
15
92
6
1
Order By: Relevance
“…In Han et al (1992), Gonzalez-Ronquillo et al (2003) and Moorby et al (2006), lower DM intake, digestibility and milk yield could have been responsible for lower MCP production, and therefore lower AL concentrations, while very high urine volumes diluted AL concentration (mg/L) in Valadares et al (1999). However, when DM intake, milk yield and urine volumes similar to ours were reported (Vagnoni and Broderick, 1997;Reynal and Broderick, 2005), AL concentrations are consistent among studies.…”
Section: Potential Impacts Of Differences In Dietary Cp Profilesupporting
confidence: 60%
See 3 more Smart Citations
“…In Han et al (1992), Gonzalez-Ronquillo et al (2003) and Moorby et al (2006), lower DM intake, digestibility and milk yield could have been responsible for lower MCP production, and therefore lower AL concentrations, while very high urine volumes diluted AL concentration (mg/L) in Valadares et al (1999). However, when DM intake, milk yield and urine volumes similar to ours were reported (Vagnoni and Broderick, 1997;Reynal and Broderick, 2005), AL concentrations are consistent among studies.…”
Section: Potential Impacts Of Differences In Dietary Cp Profilesupporting
confidence: 60%
“…However, Chizzotti et al (2008) reported that heavier animals have lower body protein content, and therefore lower urine CR outputs per unit BW. The average BW of the cows in our current study was higher (673 versus 627 and 560 kg from Moorby et al, 2006 andGonzalez-Ronquillo et al, 2003 respectively), but the BCS was relatively lower than in these studies. Since lean animals with a lower BCS may have a higher urine CR concentration per unit BW, expressing CR values as a function of metabolic BW converges the CR values among studies.…”
Section: Potential Impacts Of Differences In Dietary Cp Profilecontrasting
confidence: 38%
See 2 more Smart Citations
“…( (( Total daily purine derivative (PD) excretion (mmol/d) is the sum of PD excreted in urine and milk of lactating dairy cows (Chen and Gomes, 1992), and was estimated assuming allantoin is 0.906 of total PD in urine (obtained from values reported by Vagnoni and Broderick, 1997;Valadares et al, 1999;Gonzalez-Ronquillo et al, 2003;Reynal & Broderick, 2005;Moorby et al, 2006) and PD excretion in milk is a constant 0.05 of urine PD excretion (Chen and Gomes, 1992).…”
Section: Calculationsmentioning
confidence: 99%